2008
DOI: 10.2140/gt.2008.12.1
|View full text |Cite
|
Sign up to set email alerts
|

A desingularization of the main component of the moduli space of genus-one stable maps into ℙn

Abstract: A desingularization of the main component of the moduli space of genus-one stable maps into P n RAVI VAKIL ALEKSEY ZINGERWe construct a natural smooth compactification of the space of smooth genus-one curves with k distinct points in a projective space. It can be viewed as an analogue of a well-known smooth compactification of the space of smooth genus-zero curves, that is, the space of stable genus-zero maps S M 0;k .P n ; d /. In fact, our compactification is obtained from the singular space of stable genus-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
133
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(136 citation statements)
references
References 27 publications
1
133
0
Order By: Relevance
“…, n} and H k ( i∈I X i , Q) = 0 for every odd k < N. Let . Here the first equality holds by definition, the second one by [25], Lemma 2.3 (2), and the third one by [25], Lemma 2.3 (1). Now, it is well-know how to compare cohomology groups after a blow-up along a smooth subvariety of an orbifold (see [11], p. 605 and Proposition on p. 606, and [14], footnote on p. 514, for the orbifold case).…”
mentioning
confidence: 98%
See 4 more Smart Citations
“…, n} and H k ( i∈I X i , Q) = 0 for every odd k < N. Let . Here the first equality holds by definition, the second one by [25], Lemma 2.3 (2), and the third one by [25], Lemma 2.3 (1). Now, it is well-know how to compare cohomology groups after a blow-up along a smooth subvariety of an orbifold (see [11], p. 605 and Proposition on p. 606, and [14], footnote on p. 514, for the orbifold case).…”
mentioning
confidence: 98%
“…However, at least in the case g = 1, the beautiful construction performed in [25] has recently opened a new frontier to the research in the field. Namely, in [25] it is shown that the closure M 0 1,n (P r , d) of the stratum M 0 1,n (P r , d) corresponding to stable maps with smooth domain allows an orbifold desingularizationwhich can be explicitely described as a sequence of blow-ups along smooth centers. Moreover, the natural (C * ) r+1 -action on M 0 1,n (P r , d)…”
mentioning
confidence: 99%
See 3 more Smart Citations